Educators' experiences and perspectives of child weight discussions with parents in primary school settings - Nia Coupe; Sarah Peters; Matilda Ayres; Katie Clabon; Alexandra Reilly; Anna Chisholm (BMC, 2022)
Abstract Background The role of schools in addressing rising childhood obesity levels has been acknowledged, and numerous diet- and physical activity-related interventions exist. Aside from formal interventions, opportunistic parent-educator conversations about child weight can arise, particularly in primary school settings, yet little is known about how useful these are. This study aimed to understand the utility of child weight related conversations with parents through exploring educators' experiences and perspectives. Methods This qualitative study consisted of semi-structured interviews conducted with primary school teaching staff in the United Kingdom (N = 23), recruited through purposive and subsequent snowball sampling. Interviews were audio-recorded, transcribed, and analysed using thematic analysis. Results Participants identified opportunities and need for child weight discussions in schools. However, conversations were prevented by the indirect and sensitive nature of conversations, and educators' professional identity beliefs. Using pre-existing face-to-face opportunities, good parent-teacher relationships and holistic approaches to child health and wellbeing were reported as important in optimising these conversations. Conclusions Whilst educator-parent child weight discussions are necessary, discussions are highly challenging, with contradictory views on responsibility sometimes resulting in avoidance. Educators' roles should be clarified, and communication training tailored to increase teacher confidence and skills. Current social distancing will likely reduce opportunistic encounters, highlighting a need to further improve communication routes.